From the modernist annex : American women writers in museums and libraries - Roffman, Karin (Book collections on Project MUSE., 2010)
In the 19th and early 20th centuries, the majority of women were forced to seek their education outside the walls of American universities. Many turned to museums and libraries, for their own enlightenment, for formal education, and also for their careers. In Roffman's close readings of four modernist writers--Edith Wharton, Nella Larsen, Marianne Moore, and Ruth Benedict--she studied the that modernist women writers were simultaneously critical of and shaped by these institutions. From the Modernist Annex offers new and critically significant ways of understanding these writers and their texts.